Transformational Leadership as the Basis of Public Service - Edvard Alif; Dudi Mustofa; Hadiat (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
AbstractTransformational leadership plays a crucial role in improving the effectiveness of public services in Indonesia. This leadership style emphasizes the leader's ability to inspire, motivate, and empower subordinates to work more optimally in achieving organizational goals. In the public service sector, transformational leadership is crucial because it creates a more positive work culture, increases employee morale, and encourages innovation and collaboration in providing public services. Research shows that leaders who implement transformational leadership can build more harmonious working relationships, increase employee participation, and create a more open and collaborative organizational environment. Furthermore, transformational leadership also influences the quality of public services because leaders are able to provide role models, direction, and support that encourage employees to work professionally and responsibly. This condition has an impact on increasing organizational effectiveness and the quality of service perceived by the public. Thus, transformational leadership not only plays a role in strengthening organizational performance but also plays a crucial role in driving positive change in the public service environment. Through visionary, communicative leadership that is able to build work motivation, public service organizations can develop better and be able to provide quality, responsive services that are in line with community needs.Keywords: Transformational Leadership, Public Service.